ASSIGNMENT TEST TASKS WITHIN TECHNICAL SUBJECTS - FILIPEK, Josef (Trends in education, 2012)
The most frequently used type of tasks in didactical tests are test tasks with a choice of the correct answer. However, there some technical applications, such as diagrams of metal systems, in which assignment tasks are more convenient. The advantage of assignment tasks is that they minimize the risk of guessing the correct answer. Moreover, a single test task can contain hundreds of items at the same time not at the expense of clarity.
Keywords: assignment tests; constitution diagram; animations.